Burden and cost of illness in patients with juvenile idiopathic arthritis. Issue 7 (11th June 2004) - Minden, K; Niewerth, M; Listing, J; Biedermann, T; Schöntube, M; Zink, A
Abstract : Objective: To estimate the cost of illness in an incidence based cohort of patients with juvenile idiopathic arthritis. Methods: Direct costs (healthcare and non-healthcare costs) and indirect costs (productivity loss due to sick leave and work disability) were measured in 215 JIA patients, assessed on an average of 17 years after disease onset. Assessment included a clinical evaluation, a structured interview, and two self completion questionnaires. Annual direct costs were estimated based on the reported use of healthcare services and resources, using average unit prices. Indirect costs were estimated from the number of work days missed—that is, using the human capital approach. Results: The mean total cost of late JIA was estimated to be €3500 per patient and year, of which the direct cost contributed more than half. Patients with still active disease (55%) incurred the major share (90%) of the cost. They had a mean total cost of €5700 per patient year, with those under rheumatological care incurring a cost of €9300. Having a certain JIA subgroup, functional disability, or receipt of specialised care independently contributed to the total cost in active JIA. Highest mean total costs were found in active seropositive polyarthritis (€17 000) and extended oligoarthritis (€11 000), while the lowest were found in active enthesitis related arthritis (€1500) and persistent oligoarthritis (€2700). Conclusions: Estimated 12 month costs in late JIA are considerable, differing among the various JIA subgroups. Treatment strategies in JIA should be analysed for their cost effectiveness in the long term.